Analisa Dampak Volume Lalu Lintas dan Estimasi Berat Kendaraan Terhadap Umur Layanan Jalan - Utari, Satriani Nur; Nurdin, Abd. Rahim; Mallawangeng, Tamrin (Program Studi Teknik Sipil Universitas Bosowa, 2025)
The Pare-Pare – Sidrap road section is a National Road that connects several districts/cities in South Sulawesi Province, such as Enrekang, Tanah Toraja, Wajo and Soppeng Regencies. Apart from that, there are also vehicles that use this road to the provinces of Southeast Sulawesi and Central Sulawesi, so that many two-wheeled and four-wheeled vehicles pass through it, both light and heavy vehicles. Rapid economic growth triggers increasing growth in traffic volumes and vehicles with excessive loads lead to a decrease in road service life. This research aims to analyze the impact of traffic volume and estimated vehicle weight on road service life on the Pare-Pare – Sidrap road section and analyze the type of damage. This research is a cumulative analysis of Equivalent Single Axle Load for 10 years. The results of this research show that the Cumulative Equivalent Single Axle Load overload value is 33,376,700.74, which is greater than the planned Cumulative Equivalent Single Axle Load of 22,391,758.83. So there was a reduction in the plan age of 2.66 years, which should have been 10 years to 7.34 years. The types of damage found on these road sections are potholes, crocodile cracks, longitudinal cracks, grain release, depression, and bleeding.